(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In areas where there is not enough fresh water, it is natural that the health of the population is under threat. The article highlights the importance of water for human life, animal and plant life, its quality, the uneven location of sources in our country, sources of pollution.